Comparative transcriptome analysis reveals key pathways and regulatory networks in early resistance of Glycine max to soybean mosaic virus - Li, Han; Liu, Jinyang; Yuan, Xingxing; Chen, Xin; Cui, Xiaoyan (Frontiers in Microbiology, 2023)
As a high-value oilseed crop, Soybean [Glycine max (L.) Merr.] is limited by various biotic stresses during its growth and development. Soybean mosaic virus (SMV) is a devastating viral infection of soybean that primarily affects young leaves and causes significant production and economic losses; nevertheless, the synergistic molecular mechanisms underlying the soybean response to SMV are unknown. Therefore, we performed RNA sequencing on resistant and susceptible soybean lines infected with SMV at different time points to determine the molecular mechanism of resistance to SMV. When the clean reads were aligned to the Glycine max reference genome, a total of 36,260 genes were identified as expressed genes and used for further research. Most of the differentially expressed genes (DEGs) associated with resistance were found to be enriched in plant hormone signal transduction and circadian rhythm, according to KEGG enrichment analysis. Most of the Ca 2+ signaling-related DEGs enriched in plant-pathogen interaction negatively influence SMV resistance. Furthermore, depending on different downstream proteins, the MAPK cascade was involved in either resistant or susceptible responses to SMV. The phytochromeinteracting factor (PIF)-cryptochrome (CRY)-R protein module and the MEKK3/MKK9/MPK7-WRKY33-CML/CDPK module were found to play essential roles in the soybean response to SMV based on protein-protein interaction prediction. In addition to the well-known roles of salicylic acid and jasmonic acid in plant disease resistance, most auxin-related DEGs were also resistance-response genes to SMV. Our findings provide insight into the molecular processes by which soybean responds to SMV and have the potential to improve legume resistance to viral infection.